Career development of English and Italian high school students in uncertain times: a narrative approach. Issue 5 (3rd September 2021) - Di Palma, Tiziana; Reid, Hazel
ABSTRACT : To develop a career is considered a central task for adolescents. The aim in the present study was to explore the content and process of career development and meaning making processes using a narrative approach. As a convenience sample, participants were 20 Italian students attending their last two years of high school and 23 English students attending sixth form education. Students in both groups produced written narratives using the same prompt. Analysis indicated that most of the students are still at a development stage of "exploration", although there appear to be cultural differences. However, those who explored personal values, interests and passions, and had early work experiences, showed clearer career development.